2001
DOI: 10.1007/s003840100302
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition and apoptosis induced by P2Y2 receptors in human colorectal carcinoma cells: involvement of intracellular calcium and cyclic adenosine monophosphate

Abstract: Extracellular nucleotides induce apoptosis and inhibit growth of colorectal cancer cells. To understand the underlying signaling pathways, we investigated the role of nucleotide-sensitive P2 receptors and focused on the receptor-mediated signaling of intracellular Ca2+ and cyclic adenosine monophosphate (cAMP) in two colorectal carcinoma cell lines (HT29, Colo320 DM). Expression and functionality of P2 receptor subtypes evaluated by RT-PCR and [Ca2+]i imaging revealed that solely metabotropic P2 receptors of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 42 publications
5
61
0
Order By: Relevance
“…UTP caused an overall increase in the number of viable cells, which is contrary to the findings of other groups investigating oesophageal and colon cancer [11,12], but concordant with the recognized growthstimulatory effects of P2Y receptor subtypes as previously described [14].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…UTP caused an overall increase in the number of viable cells, which is contrary to the findings of other groups investigating oesophageal and colon cancer [11,12], but concordant with the recognized growthstimulatory effects of P2Y receptor subtypes as previously described [14].…”
Section: Discussionsupporting
confidence: 86%
“…Extracellular nucleotides, such as ATP, have previously been shown to be involved in the control of cell growth in various malignancies including oesophageal [11], colon [12], ovarian [13] and hormone-refractory prostate cancers [7]. This trophic response has been found to be mediated via P2 receptor subtypes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In human endometrial cancer cell lines, ATP was found to be associated with a significant suppression of cell proliferation through a signaling pathway involving mobilization of cytosolic stored Ca 2ϩ (19). In human colorectal carcinoma cells, extracellular ATP induced growth inhibition and apoptosis through [Ca 2ϩ ] i -or cAMP-mediated signaling (20). Of the many biological functions known to be exerted by extracellular ATP, cellular apoptosis or antiproliferation appears to be widespread rather than an exception.…”
mentioning
confidence: 99%